Extracellular vesicles derived from head and neck squamous cells carcinoma inhibit NLRP3 inflammasomes - Luiza Zainotti Miguel Fahur Bottino; Dorival Mendes Rodrigues-Junior; Ingrid Sancho de Farias; Laura Migliari Branco; N. Gopalakrishna Iyer; Gabriela Estrela de Albuquerque; André Luiz Vettore; Karina Ramalho Bortoluci (Current Research in Immunology, 2021)
The content of tumor-derived extracellular vesicles (EVs) can regulate the tumor microenvironment and functionally acts in favor of cancer aggressiveness. To better elucidate the role of EVs in the interplay between immune system and tumor microenvironment, the purpose of this study was to analyze the effect of head and neck squamous cells carcinoma (HNSCC)-derived EVs on the modulation of inflammasomes - mediators of pyroptosis and secretion of inflammatory factors by macrophages. Our results showed that macrophages treated with the Vesicular Secretome Fraction (VSF) isolated from patient-derived HNSCC presented a reduction in the secretion of mature IL-1β and caspase-1 without affecting cell viability. An analysis of the protein content of HNSCC-derived VSF by antibody array revealed that some of the most expressed proteins share a correlation with Transforming Growth Factor-beta (TGF-β) activity. Since TGF-β is related to the inhibition of the NF-kB-related pathways, including those required for the priming phase of the inflammasomes, we sought to evalute the interference of the VSF in the induction of inflammasome components. In fact, HNSCC-derived VSF inhibited the induction of pro-IL-1β and pro-caspase-1 proteins and NLRP3 gene expression during the priming phase of inflammasome activation. Thus, our findings contribute to a better understanding of how tumor-derived EVs modulate inflammatory response by demonstrating their role in inhibiting NLRP3 inflammasomes.